Transnational connections and personal ties: theorizing the Philippine overseas foreign worker experience - Hardy, Jennifer (My University, 2013)
This thesis examines the Philippine overseas foreign worker (OFW) experience through a lens of connection, a new framework. A platform of connection situates the individual OFW as the authority of her experience and explores the connections she identifies as significant values and/or attachments. The framework is rooted in theories of home, travel, and a politics of location, and is employed here to examine written cultural productions by and about OFWs. Source text includes fiction from the collection Mga Hibla ng Pangarap ("Strands of Dreams") and non-fiction from bloggers who entered the Pinoy Expat Blog Awards (PEBA) competition from 2008- 2011. These cultural productions detail connections that flow across miles and throughout life changes. These connections reveal a wider migration narrative that is individuated, complex, and emotional, yet is inextricably entwined with broad forces such as globalization and the Philippine government.
Theoretical frameworks of transnational migration -- "When we bend, it hurts": personal connections of the OFW -- Connections to technology as a means of understanding connections to the nation-state and globalization
Thesis (M.S.) - Towson University, 2012.